2021
DOI: 10.1021/acsami.0c21681
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Programmable DNA Nanotrain for Activatable Hypoxia Imaging and Mitochondrion-Targeted Enhanced Photodynamic Therapy

Abstract: Programmable DNA-based nanostructures (e.g., nanotrains, nanoflowers, and DNA dendrimers) provide new approaches for safe and effective biological imaging and tumor therapy. However, few studies have reported that DNA-based nanostructures respond to the hypoxic microenvironment for activatable imaging and organelle-targeted tumor therapy. Herein, we innovatively report an azoreductase-responsive, mitochondrion-targeted multifunctional programmable DNA nanotrain for activatable hypoxia imaging and enhanced effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It is very important to explore the fluorescence quenching mechanism in the noncovalent hypoxia imaging system. Currently, most of the hypoxia imaging probes are covalent systems and are based on the fluorescence quenching mechanism of ultrafast photoinduced isomerization of azo groups or Förster resonance energy transfer (FRET). ,,, Due to the noncovalent interaction other than covalent conjugation between SCD/ 1 and Rho123, it is impossible that the fluorescence quenching of Rho123 was caused by the fast conformation change of azobenzene. , As shown in Figure S6, there was no appreciable overlap between the absorption spectrum of SCD/ 1 and the fluorescence emission spectrum of Rho123, excluding the FRET quenching mechanism. We speculated that the fluorescence quenching of Rho123 may be caused by 1 through the photoinduced electron transfer (PET) mechanism .…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is very important to explore the fluorescence quenching mechanism in the noncovalent hypoxia imaging system. Currently, most of the hypoxia imaging probes are covalent systems and are based on the fluorescence quenching mechanism of ultrafast photoinduced isomerization of azo groups or Förster resonance energy transfer (FRET). ,,, Due to the noncovalent interaction other than covalent conjugation between SCD/ 1 and Rho123, it is impossible that the fluorescence quenching of Rho123 was caused by the fast conformation change of azobenzene. , As shown in Figure S6, there was no appreciable overlap between the absorption spectrum of SCD/ 1 and the fluorescence emission spectrum of Rho123, excluding the FRET quenching mechanism. We speculated that the fluorescence quenching of Rho123 may be caused by 1 through the photoinduced electron transfer (PET) mechanism .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Then, NADPH and rat liver microsomes (the specific composition and description of these rat liver microsomes are provided in Table S3, ESI †) containing AzoR were employed to mimic hypoxia conditions in vitro. 13,15 Fourier-transform infrared (FTIR) spectroscopy analysis confirmed that the NQN of BHQ2 was successfully reduced to amino groups through reduction reaction under hypoxic conditions (Fig. S5, ESI †).…”
mentioning
confidence: 89%
“…When the content of O 2 in the microenvironment drops, highly-expressed AzoR gradually reduces the azo bond in BHQ2 to amino groups, followed by the diminished quenching effect of BHQ2. 15 In this case, the quenched fluorescence of Cy5 would be restored, which is suitable for monitoring O 2 levels. In the case of a drop in pH, the I-motif fragment in the nanospring would fold into a quadruple-helix structure and thus cause the nanospring to change from the relaxation to contraction state.…”
mentioning
confidence: 99%
“…Due to the presence of the quencher, the cyanine fluorescence and the 1 O 2 production of the PS are limited. However, when the nanoconstruct is internalized, the aza-reductase expressed by hypoxic cells cleaves off the quencher, thus restoring the properties of the dyes, enabling a selective PDT approach [ 308 ].…”
Section: How To Tame the Bulletmentioning
confidence: 99%